Economic Changes in Poland during the Time of Covid-19 - Andrzej GRANDYS; Grzegorz SZYMANSKI (Communications of International Proceedings, 2021)
The world has faced a challenge of unprecedented scale and intensity. Today, the threat and the consequences of the Covid-19 pandemic are the most significant economic, political and social challenges. According to the reports of the Federation of Polish Entrepreneurs, the service sector suffered the greatest losses, it is affected by the greatest restrictions. On the other hand, industry, construction, transport and IT services lost the least due to successive waves of the pandemic. The severity and pervasiveness of its impact is an unprecedented phenomenon. Assessment of the situation in selected areas (labour market, banking, trade, education) could help to identify some of the effects of the pandemic but also threats and opportunities. It seems that the pandemic crisis has exposed areas of ignorance and has become a motivating factor for increasing cognitive efforts. The study aims to focus on and present, i.a., several functional areas of business entities.
Keywords: Economic changes; Covid-19; Poland; economic crisis; pandemic.